2018
DOI: 10.1097/mat.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Bilirubin Levels, NT-pro-BNP, and Lactate Predict Mortality in Long-Term, Severely Ill Respiratory ECMO Patients

Abstract: Mortality in patients treated with extracorporeal membrane oxygenation (ECMO) is high. Therefore, it is crucial to better understand conditions that are associated with mortality in ECMO patients. In this retrospective analysis, we observed 51 patients treated with high-flow ECMO in 2013 and 2014 at our center. We recorded laboratory values and intensive care procedures. The hypothesis of bilirubin being a predictor of mortality during ECMO treatment was initially addressed. Therefore, laboratory values were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 11 publications
2
19
1
3
Order By: Relevance
“…Hyperbilirubinaemia, an independent predictor of poor outcomes, occurs due to a combination of extracorporeal haemolysis and liver dysfunction [ 57 ]. Elevated alkaline phosphatase, lactate and BNP are associated with poor outcomes [ 58 ], while elevated AST and ALT levels do not seem to be predictive. In patients on ECMO, studies have shown that baseline Model for End stage Liver Disease, United Network for Organ Sharing modification (MELD UNOS) [ 59 ] and Model for End Stage Liver Disease score excluding INR (MELD XI) [ 60 ] scores can predict outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperbilirubinaemia, an independent predictor of poor outcomes, occurs due to a combination of extracorporeal haemolysis and liver dysfunction [ 57 ]. Elevated alkaline phosphatase, lactate and BNP are associated with poor outcomes [ 58 ], while elevated AST and ALT levels do not seem to be predictive. In patients on ECMO, studies have shown that baseline Model for End stage Liver Disease, United Network for Organ Sharing modification (MELD UNOS) [ 59 ] and Model for End Stage Liver Disease score excluding INR (MELD XI) [ 60 ] scores can predict outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Kaestner ve ark. 'nın [29] çalışmasında ise, bilirubin, laktat ve N-terminal pro-brain natriüretik peptid ECMO sırasındaki mortalite ile ilişkilendirilmiştir. Ancak, bu çalışmada bilirubin değerleri yalnızca en yüksek olduğu dönemde çalışılmıştır.…”
Section: Verilerin İstatistiksel Analiziunclassified
“…noch laufende Reanimation sind wichtige Aspekte. Laborchemisch spielen das Laktat, das akute Nierenversagen oder ein Leberversagen also der Ausdruck des sich entwickelnden MODS (Multiorgandysfunktionssyndrom)eine wesentliche Rolle [4,15]. Auch die Aufnahme in ein großes Krankenhaus mit allen Möglichkeiten der Versorgung des kardiogenen Schockes scheint nicht nur zu einem vermehrten Einsatz der Systeme zu führen, sondern auch die Mortalität günstig zu beeinflussen [3,4].…”
Section: Kur Zgefasstunclassified
“…Dadurch können bei liegenden ECLS-Schleusen Entscheidungshilfen für die antegrade Punktion gegeben werden [38,39]. Nach metaanalytischen Daten unter Einschluss von 1866 Patienten liegt die Rate an Beinischämien bei 16,9 % [ CI 12,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]6], an Fasziotomien oder Kompartment-Syndromen bei 10,3 % [CI 7,3-14,5] und die Rate an Amputationen bei 4,7 % [CI 2,3-9,3] [40].…”
Section: Monitoring Komplikationenunclassified